2009
DOI: 10.1111/j.1365-2133.2009.09572.x
|View full text |Cite
|
Sign up to set email alerts
|

Successful retreatment with alitretinoin in patients with relapsed chronic hand eczema

Abstract: The majority of patients with CHE who previously achieved 'clear' or 'almost clear' hands following treatment with alitretinoin 30 mg per day also responded to a second course of treatment. Retreatment was well tolerated. Intermittent treatment with alitretinoin is suitable for the long-term management of CHE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
76
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(86 citation statements)
references
References 10 publications
3
76
1
6
Order By: Relevance
“…In our case the second and third therapeutic course of alitretinoin (30 mg daily) was necessary to completely heal the skin lesions. This is consistent with the data from a recently reported trial on chronic hand eczema [3] . The authors of this study demonstrated that alitretinoin at the dose of 30 mg daily reinduced response in the majority of patients who had relapsed within 6 months following successful treatment with an initial course of alitretinoin.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In our case the second and third therapeutic course of alitretinoin (30 mg daily) was necessary to completely heal the skin lesions. This is consistent with the data from a recently reported trial on chronic hand eczema [3] . The authors of this study demonstrated that alitretinoin at the dose of 30 mg daily reinduced response in the majority of patients who had relapsed within 6 months following successful treatment with an initial course of alitretinoin.…”
Section: Discussionsupporting
confidence: 83%
“…The most frequent adverse effects of alitretinoin include mucocutaneous dryness and headache [3] . The latter is dose dependent and often disappears with dose reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Although 9cRA appears to be a promising agent for prevention or treatment of prostate cancer on the basis of these results and animal data, clinical studies with 9cRA have demonstrated that oral intake is associated with dose-limiting side effects (Lawrence et al, 2001;Bissonnette et al, 2010). As a therapeutic agent, these side effects could be acceptable, but they render 9cRA unacceptable for prevention, particularly because the effects of retinoids are reversible (Esquenet et al, 1996) and sustained consumption would be necessary to maintain the protective effect.…”
Section: Discussionmentioning
confidence: 89%
“…Stwierdzono całkowite lub prawie całko-wite ustąpienie zmian u 48% leczonych największą dawką (30 mg/dobę) w porównaniu z 28% pacjentów leczonych dawką 10 mg/dobę i 17% pacjentów z grupy otrzymujących placebo [27]. W 2009 roku przeprowadzono dodatkowe badanie oceniające skuteczność powtórnego włączenia terapii alitretynoiną u osób z nawracającym wypryskiem rąk i uzyskano obiecujące wyniki [28]. Wykazano również skuteczność leku w leczeniu odmian chłoniaków T--komórkowych skóry [29,30] oraz ziarniniaka ropotwórczego [31].…”
Section: Skuteczności Alitretynoinyunclassified